2004
DOI: 10.1149/1.1784053
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed CVD of Tungsten Thin Film as a Nucleation Layer for Tungsten Plug-Fill

Abstract: Tungsten ͑W͒ thin film as a nucleation layer for a W plug-fill process was deposited using a modified chemical vapor deposition ͑CVD͒ called pulsed CVD, and properties of the films were investigated. Basically, the deposition stage was composed of four separate steps for one deposition cycle: (i) reaction of WF 6 with SiH 4 ; (ii) inert gas purge; (iii) SiH 4 exposure without WF 6 ; and (iv) inert gas purge. A higher deposition rate, ϳ1.5 nm/cycle, was obtained as compared to that of atomic layer deposition ͑A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…For Ni 3 N it is observed that the growth is low at short (Ni(thd) 2 substrates. [24] The curve in Figure 4A is expected for a deposition process with nucleation problems.…”
Section: Growth Per Pulse Metal Precursormentioning
confidence: 96%
See 3 more Smart Citations
“…For Ni 3 N it is observed that the growth is low at short (Ni(thd) 2 substrates. [24] The curve in Figure 4A is expected for a deposition process with nucleation problems.…”
Section: Growth Per Pulse Metal Precursormentioning
confidence: 96%
“…In a previous work, both Cu 3 N and Ni 3 N have been deposited by CVD and atomic layer deposition (ALD) from Cu(hfac) 2 and Ni(thd) 2 , respectively, with NH 3 as the nitrogen source. [22][23][24] The CVD processes have overlapping temperature and total pressure regions to reach surface kinetics control.…”
Section: Full Papermentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years significant effort has been devoted towards developing surface acoustic wave (SAW) sensors based on WO 3 sensing films, to be used for detection of gases like NO, H 2 S, NO 2 , SO 2 , CO, CO 2 . The WO 3 films have been deposited by various techniques as magnetron sputtering [1,2,3], electrochemical deposition [4,5], chemical vapor deposition [6,7], as well as laser ablation technique [8,9,10].…”
Section: Introductionmentioning
confidence: 99%